PRAKTIK MENONTON SIARAN TELEVISI INDONESIA OLEH PENONTON ASING (Studi Perilaku Menonton dan Resepsi Siaran Televisi Indonesia oleh Mahasiswa Vietnam) - , DYAH KUSUMA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to determine the viewing practice of Indonesian television program by Vietnamese students. The viewing practice in this research is examined from two aspects. First, the viewing behaviour, consist of favourite television programs, aims, attention, place, and time of viewing practice. Second, the reception of Indonesian television programs, consist of decoding process, valuation, and reception of Indonesian television programs. This research isa qualitative research with audience study domain. The object of this research is Vietnamese students in Indonesia and they are chosen because of their viewing practice. The data are obtained by observation, in-depth interview, and literature study. The results show that: (1) Vietnamese students prefer to watch foreign television program, because it is easier to understand the message that is delivered in English, (2) the aims of the viewing practice is to get the entertainment, (3) the viewing practice strengthens the social relation betweenthe Vietnamese students and their neighbour, (4) the culture differences between Vietnam and Indonesia have a role on limiting, understanding, and valuating the Indonesian television programs, (5) the reception is categorized in preferred reading.